2017
DOI: 10.1016/j.ajhg.2017.07.004
|View full text |Cite
|
Sign up to set email alerts
|

De Novo Mutations in YWHAG Cause Early-Onset Epilepsy

Abstract: Massively parallel sequencing has revealed many de novo mutations in the etiology of developmental and epileptic encephalopathies (EEs), highlighting their genetic heterogeneity. Additional candidate genes have been prioritized in silico by their co-expression in the brain. Here, we evaluate rare coding variability in 20 candidates nominated with the use of a reference gene set of 51 established EE-associated genes. Variants within the 20 candidate genes were extracted from exome-sequencing data of 42 subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
91
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(102 citation statements)
references
References 65 publications
11
91
0
Order By: Relevance
“…Previous to this, in 2013, Allen et al In the only YWHAG series to-date, Guella et al, 2017 described four patients with de novo variants in YWHAG and suggested it as a cause of early-onset epilepsy, DEE and ID (Guella et al, 2017). In this series, the de novo variants were predicted to impair dimerization and phosphopeptide binding.…”
Section: Discussionmentioning
confidence: 90%
“…Previous to this, in 2013, Allen et al In the only YWHAG series to-date, Guella et al, 2017 described four patients with de novo variants in YWHAG and suggested it as a cause of early-onset epilepsy, DEE and ID (Guella et al, 2017). In this series, the de novo variants were predicted to impair dimerization and phosphopeptide binding.…”
Section: Discussionmentioning
confidence: 90%
“…Recent human genetic studies identified 5 heterozygous SLC1A2 (EAAT2/GLT1) mutations in patients and families with either of epileptic encephalopathy, early myoclonic encephalopathy, early-onset epileptic encephalopathy or infantile spasms (Epi4K Consortium, 2013Consortium, , 2016Guella, et al, 2017). All individuals had early-onset multiple seizure types with prominent myoclonic and tonic seizures as well as spasms.…”
Section: Discussionmentioning
confidence: 99%
“…There are five structurally distinct subtypes of Na 1 -dependent glutamate transporters, GLAST (EAAT1), GLT1 (EAAT2), EAAC1 (EAAT3), EAAT4 and EAAT5. Recent genetic studies in human populations have suggested that de novo mutations in EAAT2 (GLT1) cause early-onset epilepsy with multiple seizure types (Epi4K Consortium, 2013, 2016Guella, et al, 2017). GLT1, which is the most prominently expressed glutamate transporter in the mammalian CNS, plays a key role in the maintenance of extracellular glutamate homeostasis to protect neurons from excitotoxicity (Coulter & Eid, 2012;Takahashi, Foster, & Lin, 2015).…”
mentioning
confidence: 99%
“…Motor features including spasticity, ataxia, and choreoathetosis are often present. 84,85 Mutations in YWHAG, encoding a member of the 14-3-3 protein family involved in intracellular signalling, protein trafficking, cell-cycle control, and apoptosis, 78 cause DEE characterized by variable seizure types (focal motor, GTCS, myoclonic, absence), ataxia, and tremor. 78,79 Genes with other cellular functions Biallelic mutations in UBA5, a gene involved in protein posttranslational modification, cause DEE including Ohtahara syndrome, West syndrome, or myoclonic jerks, and axial or peripheral hypotonia.…”
Section: Sodium Channel Genesmentioning
confidence: 99%